2015
DOI: 10.1002/jsfa.7110
|View full text |Cite
|
Sign up to set email alerts
|

Effects of processing conditions and formulation on spray drying of sour cherry juice concentrate

Abstract: Spray-dried sour cherry powder with high yield (>85%) and high Tg (60 °C) was obtained using the following conditions: 150 °C inlet temperature, 30% pump setting, 25% sour cherry content and maltodextrin DE12 as carrier.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(40 citation statements)
references
References 24 publications
(80 reference statements)
5
31
0
2
Order By: Relevance
“…The product stickiness in the drying chamber is the preeminent cause for the decreased powder recovery percentage …”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The product stickiness in the drying chamber is the preeminent cause for the decreased powder recovery percentage …”
Section: Resultssupporting
confidence: 92%
“…The product stickiness in the drying chamber is the preeminent cause for the decreased powder recovery percentage. 55 The raised air temperature (from 100°C to 160°C) increases the powder recovery percentage from 11.00 to 23.65%. These observations were in agreement with those of Bilancetti et al, 12 Muzaffar et al, 44 Bazaria et al, 56,57 and Mahdi et al 58 However, operating under a decreased air temperature did not allow for a powder collection along the drying chamber, as reported by Alamilla-Beltran et al 59 At higher drying temperatures, heat and mass transfer are more effective.…”
Section: Powder Recoverymentioning
confidence: 99%
“…A similar observation was made in the case of amla and Cagaita juice powders pointing to a concentration effect of the carrier on the properties of the final products [45,46]. Previously, Daza et al [39] and Tonon et al [47] indicated a strong influence of the type of carrier on the retention of total polyphenolic compounds in acai and Cagaita juice powders. In the current study, powders obtained from the formulation containing maltodextrin had better retention of TPC after freeze-drying when compared to powders with inulin and maltodextrin-inulin.…”
Section: Chemical Propertiessupporting
confidence: 69%
“…The content of total polyphenolic compounds (TPC) determined by the spectrophotometric method in cranberry cv. Pilgrim was 120 mg/100 g [39]. In the present study, the TPC content ranged from 127.7 up to 354.1 mg GAE/100 g DM for powders obtained using 35% maltodextrin and 15% maltodextrin after freeze-drying.…”
Section: Chemical Propertiesmentioning
confidence: 45%
See 1 more Smart Citation